Comparing Face-to-Face, Blended and Online Teaching Approaches for Practical Skill Acquisition: A Randomised Controlled Trial - Forde, Cuisle (My University, 2024)
Introduction: The efficacy of blended and online teaching methods for practical skill acquisition remains ambiguous, particularly for skills requiring haptic awareness and/or sensory training. This study aims to compare three teaching methods (face-to-face, blended, online) for the acquisition of skills requiring sensory learning and haptic awareness. A secondary aim was to explore student experience of each teaching approach. Design: A post-test only randomised controlled trial. Methods: Forty-seven participants chose between learning two skills: manual measurement of blood pressure during exercise (BPM) and/or skin fold measurement using callipers (SKM). Participants were randomised to one of three learning groups: face-to-face (n = 23), blended (n = 22) and online (n = 26). Assessors determined skill competency during an in-person skill demonstration session. A survey captured student experiences. Results: For SKM, there was a statistically significant difference in skill competency between the online learning group (17% achieved competency) and both the face-to-face (75% achieved competency; p = 0.011) and blended (89% achieved competency; p = 0.001) learning groups. For BPM, the online group had the lowest percentage of participants achieve overall skill competency. Both knowledge-based and sensory-based sub-competencies were negatively affected by the online learning method. For both skills, students in the face-to-face and blended learning group were significantly more confident in their knowledge and their ability to perform the skill in a clinical setting, compared to the online learning group. Conclusion: Both face-to-face and blended teaching methods were more effective at leading to skill acquisition and were preferred by students when compared to a fully online teaching method.
PUBLISHED
Keywords: Clinical skill; Online education; Practical education; Student voice; Digital Engagement; Inclusive Society; Allied Health Education; Clinical Education; Education research; Higher Education; Medical Education